2003
DOI: 10.1046/j.1420-9101.2003.00597.x
|View full text |Cite
|
Sign up to set email alerts
|

Fitness effects of female mate choice: preferred males are detrimental for Drosophila melanogaster females

Abstract: The evolution of female mate choice, broadly defined to include any female behaviour or morphology which biases matings towards certain male phenotypes, is traditionally thought to result from direct or indirect benefits which females acquire when mating with preferred males. In contrast, new models have shown that female mate choice can be generated by sexual conflict, where preferred males may cause a fitness depression in females. Several studies have shown that female Drosophila melanogaster bias matings t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
119
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(126 citation statements)
references
References 111 publications
(230 reference statements)
4
119
3
Order By: Relevance
“…2). These results suggest that the attractiveness of male phenotypes from the different lines is likely to also be affected by factors other than WIPs alone, consistent with previous studies (20)(21)(22). Alternatively, but certainly not mutually exclusively, females could, at least to some extent, detect variation in male WIP-phenotypes even in the environment with white background.…”
Section: Resultssupporting
confidence: 89%
“…2). These results suggest that the attractiveness of male phenotypes from the different lines is likely to also be affected by factors other than WIPs alone, consistent with previous studies (20)(21)(22). Alternatively, but certainly not mutually exclusively, females could, at least to some extent, detect variation in male WIP-phenotypes even in the environment with white background.…”
Section: Resultssupporting
confidence: 89%
“…Interestingly, these findings are at odds with previous studies that have found male body size and harm to be associated with each other [19,20]. However, in these studies body size variation was achieved by manipulating larval densities/ nutrition [19,20], while our males were reared under the standardized conditions that the IV population has evolved under for decades. It is possible that phenotypic correlations may have arisen owing to trade-offs resulting from this methodology.…”
Section: Discussioncontrasting
confidence: 64%
“…In fact, the ''inadvertent selection'' alternative implies that mating with large males is more harmful to females, otherwise there would be no reason to expect inadvertent selection for low body size to produce a correlated response in terms of decreased harmfulness. Indeed, the existence of such association was experimentally corroborated in Drosophila melanogaster (Friberg and Arnqvist 2003). Thus, in the absence of inadvertent evolution for reduced body size, it seems that smaller size of monogamous males could result from selection for reduced male harmfulness, rather than the other way round.…”
Section: Discussionmentioning
confidence: 89%